Private Investment Demand Function in Bangladesh: An ARDL Approach - Bal, Harun; Mamun, Abdullahil; Mowla, Mohammad Masrurul; Hoque, Nazamul; Bhuiyan, Md. Zahid Hossain (Asian Business Review, 2019)
Investment, as an addition to the existing physical stock of capital, contributes to the growth of Bangladesh economy in a decisive way. Therefore, factors that determine the private investment need to be studied in order to frame policies to manage them so as to achieve the desired capital stock for the economy to accomplish the much higher GDP growth objective in coming years. The study, thus, is an attempt to estimate the private investment demand function of Bangladesh. It employees the ARDL bounds testing approach to investigate the relationship between private investment spending and its regressors, namely, real income, rental cost of capital, foreign direct investment and exchange rate relying on data for the period 1980-2017. The study identifies a long-run equilibrium relationship between private investment spending and its determinants. The determinants are found to have conventional signs- while a rise in real income boosts private investment spending, a rise in the rental cost of capital hurts it. While most of the earlier studies compared the relative role of public and private investment in economic growth of Bangladesh, studies on the factors that determine the countries investment spending is very few. Moreover, majority of the studies in the latter group focuses on determinants of gross investment in Bangladesh, while the study focuses on the domestic private investment taking most recent years’ data in the sample period.JEL Classification Codes: E20, E22